2019
DOI: 10.1007/s42770-019-00065-7
|View full text |Cite
|
Sign up to set email alerts
|

Divergent coronaviruses detected in wild birds in Brazil, including a central park in São Paulo

Abstract: Coronaviruses are single-stranded positive-sense RNA viruses associated with important avian diseases. Their relatively high rates of mutation and recombination frequencies allow them to adapt to new hosts and ecological niches. Although Brazil has 18% of global avian species diversity, studies regarding the presence of avian viral diseases in wild birds in South America are scarce. In this study, we performed a retrospective analysis of the presence of CoVs in 746 wild birds. Oropharyngeal and cloacal swabs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
2
17
0
2
Order By: Relevance
“…showing the capacity for spillover events between bird and mammal hosts of CoVs (Barbosa et al, 2019). Other studies also found delta-CoV from Psittaciformes (Duraes-Carvalho et al, 2015) and IBV (Mass, Conn) from Columbiformes birds in Brazil (Felippe et al, 2010).…”
Section: Brazilmentioning
confidence: 88%
See 3 more Smart Citations
“…showing the capacity for spillover events between bird and mammal hosts of CoVs (Barbosa et al, 2019). Other studies also found delta-CoV from Psittaciformes (Duraes-Carvalho et al, 2015) and IBV (Mass, Conn) from Columbiformes birds in Brazil (Felippe et al, 2010).…”
Section: Brazilmentioning
confidence: 88%
“…Barbosa et al. (2019) carried out a retrospective study of the existence of CoVs in 746 wild birds whereby CoV RNA was observed and sequenced from six samples (0.8%), three of which were linked to gamma‐CoV and the other three to delta‐CoV. The research evidence indicates the finding of avian gamma‐ and delta‐CoV in birds obtained in the south‐eastern and southern regions of Brazil, more precisely in Sao Paulo and the state of Rio Grande do Sul.…”
Section: Global Distribution Of Coronavirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, it is not only Asian bats that should be covered by environmental coronavirus surveillance but also strains associated with avian hosts, including synanthropic species. A number of previous studies have already indicated that birds from different geographical areas and related to terrestrial and aquatic ecosystems serve as the reservoirs for various delta- and gammacoronaviruses ( Barbosa et al, 2019 ; Chamings et al, 2018 ; Chu et al, 2011 ; Hughes et al, 2009 ; Miłek and Blicharz-Domańska, 2018 ; Paim et al, 2019 ; Wartecki and Rzymski, 2020 ). None of these are known to be pathogenic to humans, although potential cross-species transmission must be taken into account because: i) selected strains associated with avian hosts are closely related to coronaviruses identified in mammals ( Woo et al, 2009 ), and ii) a recent bird-swine transmission of deltacoronavirus is believed to have occurred ( Lau et al, 2018 ), and recombination, which is a common phenomenon in coronaviruses, has frequently concerned the spike region which is involved in receptor binding ( Lau et al, 2018 ).…”
Section: Monitoring and Identification Of Novel Viral Agents In Animamentioning
confidence: 99%